MODEL PENINGKATAN KINERJA KARYAWAN BERBASIS GAYA KEPEMIMPINAN DAN DISIPLIN KERJA PADA PT SECURINDO PACKATAMA INDONESIA CABANG PLAZA SENAYAN [MODEL FOR ENHANCING EMPLOYEE PERFORMANCE BASED ON LEADERSHIP STYLE AND WORK DISCIPLINE AT PT SECURINDO PACKATAMA INDONESIA, PLAZA SENAYAN BRANCH] - Samcay, Samcay; Sumiaty, Raden Yeti (Perkumpulan Ahli Bimbingan dan Konseling Islam Indonesia, 2025)
This study aims to examine how leadership style and work discipline play a role in improving employee performance at PT Securindo Packatama Indonesia Plaza Senayan Branch, Central Jakarta. The scope of the study includes all employees with a sample of 90 respondents obtained through questionnaires. The method used is an associative approach with simple and multiple linear regression analysis, correlation coefficient, determination coefficient, t test, and F test. The results of the study indicate that leadership style has a positive and significant contribution to employee performance as evidenced by the regression equation Y = 25.793 + 0.375X, correlation value 0.739, determination coefficient 54.6%, and t count 10.291 which is greater than t table. Work discipline also provides a positive and significant contribution with the equation Y = 25.110 + 0.392X, correlation value 0.703, determination coefficient 49.4%, and t count 79.273. Simultaneously, both variables contribute significantly to employee performance through the equation Y = 22.968 + 0.245X₁ + 0.200X₂, a correlation value of 0.781, a coefficient of determination of 53.56%, and an F count of 68.020, which confirms the significance of the model. This finding confirms that leadership style and work discipline are important factors in strengthening employee performance at the company.